Analysis of implementation of integrated information systems in Croatian wood processing industry : Analiza primjene integriranih informacijskih sustava u hrvatskoj drvoprerađivačkoj industriji - Perić, Ivana, inženjerka drvne tehnologije (Array, 2019)
It can be said that Integrated Information Systems (IIS) are a fundamental operating tool in modern business systems and form the basis of successful company management. The goal of our research was to determine the IT level of business operations in Croatian wood processing industry and to assess how significant it has been in enhancing its business performance. A survey method was used to collect data, which resulted in gathering predominantly small and medium-sized companies. Our results indicate an average use of IIS modalities among surveyed companies. Using cluster analysis, three types of companies were identified with respect to the degree of system implementation. Analysis of financial benefits of the IIS implementation did not find any statistically significant relationship. However, subjective impressions on non-financial indicators show that companies in all three clusters see the greatest benefit of IIS in the improved inventory efficiency and sales efficiency.